Optimization of Nitrogen Rate and Planting Density for Improving Yield, Nitrogen Use Efficiency, and Lodging Resistance in Oilseed Rape - Khan, Shahbaz; Anwar, Sumera; Kuai, Jie; Ullah, Sana; Fahad, Shah; Zhou, Guangsheng (Frontiers in Plant Science, 2017)
Abstract: Yield and lodging related traits are essential for improving rapeseed production. The objective of the present study was to investigate the influence of plant density (D) and nitrogen (N) rates on morphological and physiological traits related to yield and lodging in rapeseed. We evaluated Huayouza 9 for two consecutive growing seasons (2014–2016) under three plant densities (LD, 10 plants m−2; MD, 30 plants m−2; HD, 60 plants m−2) and four N rates (0, 60, 120 and 180 kg ha-1). Experiment was laid out in split plot design using density as a main factor and N as sub-plot factor with three replications each. Seed yield was increased by increasing density and N rate, reaching a peak at HD with 180 kg N ha-1. The effect of N rate was consistently positive in increasing the plant height, pod area index, 1,000 seed weight, shoot and root dry weights and root neck diameter, reaching a peak at 180 kg N ha-1. Plant height was decreased by increasing D, whereas the maximum radiation interception (approximately 80 %) and net photosynthetic rate were recorded at MD at highest N. Lodging resistance and nitrogen use efficiency significantly increased with increasing D from 10 to 30 plants m-2, and N rate up to 120 kg ha-1, further increase of D and N decreased lodging resistance and NUE. Hence, our study implies that planting density 30 plants m−2 can improve yield, nitrogen use efficiency and enhance lodging resistance by improving crop canopy.